Seven Level Inverter Fault Mitigation Using Redundant Cell for Induction Motor Drive - B. Madhu Kiran; B. V. Sanker Ram (Institute of Advanced Engineering and Science, 2018)
Faults that might occur in inverter driven induction motor drives. In this paper, seven-level multi level inverter was taken up for testing of mitigation using redundant cell and the results were compared with five-level inverter to exhibit the performance of mitigation policy. This paper presents analysis of inverter feeding an induction motor drive when switch open and short fault occurs. When the fault occurs, the redundant cell activates and thus the drive system operates. In this paper, the function for redundant cell was explained with the results of drive system simulated in Matlab/Simulink.